Can AI Assess Clinical Competency? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of medical education is in a constant state of evolution, driven by the dual needs of ensuring the highest standards of patient care and equipp...
Keywords: AI in Medical Education and Future of Healthcare; Assess; Clinical; Competency; Artificial Intelligence; Machine Learning; Healthcare